KOMPETENSI GURU DAN KESENJANGAN MUTU PENDIDIKAN: STUDI ATAS TANTANGAN IMPLEMENTASI KURIKULUM MERDEKA - Rifqiya Zahara; Me Griselia Hariyono; Uti Muhsi Asy'ari; Munawir (STKIP Subang, 2026)
This paper explores the impact of teachers' competency in shaping educational quality disparity in the application of the Merdeka curriculum in Indonesia. In this case, the research problem relates to the disparity in quality of education due to the disparity in teacher competency, resource access, and school preparedness. The research objective is to assess the impact of teachers' competency on both curriculum application and educational disparity. A qualitative descriptive research design, complemented by a literature review approach, was adopted for this study. Based on the findings, teachers' competencies in pedagogy, professionalism, society, and personal areas play an important role in ensuring effective and learner-centered learning process. Nevertheless, the lack of uniformity in terms of competencies as well as the accessibility to resources and technology makes its optimal application impossible.